Antimicrobial Activities of Bioactive Compounds from Jatropha curcas - Zona Octarya; Fitri Refelita; Novia Rahim (Indonesian Journal of Chemical Science and Technology (IJCST), 2019)
Jatropha curcas L is widely planted in people's homes. Jatropha has many bioactive compounds, including flavonoids, saponins, tannins, and alkaloids. In this research, phytochemical tests and antimicrobial activities of sap and water extraction of Jatropha curcas L leaves on Candida albicans, Aspergillus, and Pseudomonas aeruginosa were carried out. The results of the phytochemical test of sap and water extraction of leaves showed positive results in the test of flavonoids, saponins, alkaloids and tannins. While steroid testing showed negative results. The antimicrobial capabilities of sap and water extraction of leaves to Aspergillus were 10.5 mm and 11 mm and to Pseudomonas Aeruginosa were 15 mm and 11 mm. Whereas the antimicrobial ability of sap and water extraction of leaf to Candida albicans was negative. In this case, it means that Pseudomonas aeruginosa is including microbes that are sensitive to antimicrobial origin of plants.